Analysis of factors affecting tuberculosis treatment adherence at Lesung Batu Community Health Center: A cross-sectional study - Puspita Kurnia Sari; Ali Harokan; Lilis Suryani (School of Health Sciences Al-Ma'arif, 2025)
Background Tuberculosis (TB) remains a major global health problem with high rates of morbidity and mortality, particularly in developing countries like Indonesia. One of the main challenges in TB control is the low treatment adherence among patients undergoing long-term therapy. Objective This study aimed to analyze the factors influencing tuberculosis medication adherence among patients at Lesung Batu Community Health Center.. Methods A quantitative cross-sectional study was conducted from May 8 to 27, 2025, involving 56 TB patients registered at the Lesung Batu Health Center. Total sampling was used. Data were collected using a structured questionnaire based on the Morisky Medication Adherence Scale (MMAS-8) and analyzed using Chi-square and multivariate logistic regression. Results Only 51.8% of respondents were adherent to TB medication. Bivariate analysis showed that gender (p=0.01), distance to health facilities (p=0.01), and family support (p=0.00) had significant associations with adherence. Multivariate analysis revealed family support as the most dominant factor (OR=0.16, 95% CI=0.05–0.51), indicating that patients without family support were 6.25 times more likely to be non-adherent. Conclusion Family support, proximity to health services, and male gender significantly influenced TB medication adherence. Interventions should focus on increasing family involvement and improving access to care for patients in remote areas. Primary healthcare providers are advised to implement community-based strategies that include home visits, family counseling, and cross-sectoral collaboration to enhance adherence and improve treatment outcomes.